Bad liar : a novel [large type] - Hoag, Tami (Thorndike Press large print top shelf., 2024)
"A murder victim dumped at the end of a country road is not the way sheriff's detective Nick Fourcade wants to start his week. His only lead takes him to the family of a hometown hero gone missing. Marc Mercier left for a weekend hunting trip and hasn't been seen since. Meanwhile, sheriff's detective Annie Broussard begins her day by taking on the case of B'Lynn Fontenot, a mother desperate to find her grown son. As Annie searches for Robbie Fontenot and Nick investigates the disappearance of Marc Mercier, old jealousies and fresh deceits, family loyalties gone wrong, and love turned sour all lay a twisting trail that endangers all who cross the path of a bad liar"--